Incidence of Otolaryngological Diseases in General Population: A Study in Eastern Medical College Hospital - Alam, Anwar Ul; Ullah, Md Kalim; Shakil, Mohammad; Rahman, SM Tauhidur; Ahamed, Mohammad Khaza; Sarower, Mohammad Golum (Eastern Medical College Journal, 2022)
Background: Otolaryngological diseases are serious public health problems affecting all age groups. This includes problem of hearing, speech, phonation, breathing, swallowing, smell & taste and protection of lower respiratory passage. Objective: The aim of this study was to determine the common clinical presentation and socio demographic characteristics of the patients attending in ENT outdoor. Method: This cross-sectional study was conducted among 500 patients attending in ENT outdoor in Eastern medical college Hospital, Cumilla, Bangladesh using a self-administered semi-structured questionnaire from July 2020 to September 2020. Result: In this study 44.8% were male and 55.2% female. All age group were included and majority of patients were age group of 21-30 years (28.6%). In our study 38.2% (191) of the study populations were suffering from ear diseases, and then followed by 32% (160) nose diseases and 29.8% (149) throat diseases. Common ear, nose, throat diseases were suppurative otitis media 30.37% (58), allergic rhinitis 23.13% (37), tonsillitis 31.54% (47), respectively. Conclusion: Our study provides basic information of the incidence of ENT disorders in the study area suggests that suppurative otitis media, tinnitus, foreign body ear, allergic rhinitis, nasal polyp, sinusitis, tonsillitis and pharyngitis are the most common Otolaryngological (ENT) problems in general population visiting the ENT Department of this hospital and contribute significantly to morbidity. EMCJ. January 2022; 7(1): 6-10